2013
DOI: 10.1007/s00044-013-0684-3
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of thiocarbohydrazide and carbohydrazide derivatives as possible biologically active agents

Abstract: A series of new b-isatin aldehyde-N,N 0 -thiocarbohydrazone, bis-b-isatin thiocarbohydrazones, bis-bisatin carbohydrazones was synthesized by condensation of 5-substituted isatin with thiocarbohydrazide or carbohydrazide. The chemical structures of the newly synthesized compounds were confirmed by FT-IR, 1 H NMR, and mass spectral analysis. The synthesized compounds were evaluated for in vitro antiviral activity against various strains of DNA and RNA viruses, but exhibited moderate antiviral activity compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…1,3‐Bis({(3 Z )‐2‐oxo‐2,3‐dihydro‐1 H ‐indol‐3‐ylidene]‐amino}urea 6 was formed as one of the products in the course of the reaction of 4a , 4b , 4c , 4d , 4e , 4f , 4g , 4h , 4i , 4j with 2 . The structure of 6 is further supported by characteristic IR, NMR, mass spectrometry data, and comparison with authentic sample . Moreover, the structure of 6 was confirmed ambiguously by single X‐ray structure analysis (Fig.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…1,3‐Bis({(3 Z )‐2‐oxo‐2,3‐dihydro‐1 H ‐indol‐3‐ylidene]‐amino}urea 6 was formed as one of the products in the course of the reaction of 4a , 4b , 4c , 4d , 4e , 4f , 4g , 4h , 4i , 4j with 2 . The structure of 6 is further supported by characteristic IR, NMR, mass spectrometry data, and comparison with authentic sample . Moreover, the structure of 6 was confirmed ambiguously by single X‐ray structure analysis (Fig.…”
Section: Resultsmentioning
confidence: 70%
“…Earlier, Joshi et al followed by Badawy et al have been reported that condensation of isatins with thiocarbohydrazide gave 2‐oxo‐1′,2′,4′,5′‐tetrazine‐6′‐thiones as spiro system rather than the expected thiocarbohydrazones . Latter, this work was repeated by Manda and Giangarapu and subsequently claimed that the previous work was in error and a series new β‐isatin aldehyde‐ N , N ″‐thiocarbohydrazone was synthesized by condensation 5‐substituted isatins with aldehyde thiocarbohydrazones.…”
Section: Introductionmentioning
confidence: 92%
“…The X‐ray crystal structure for 6 is shown in Figure . Compound 6 was previously synthesized from the reaction of a 1:1 mixture of thiocarbohydrazide ( 2 ) and isatin ( 4 ) in boiling ethanol in the presence of acetic acid for 2 h . Also, 6 was produced as a side product (20–27% yield) from the reaction of isatylidene malononitrile and (ylidene)thiocarbohydrazides in ethanol in the presence of piperidine at room temperature .…”
Section: Resultsmentioning
confidence: 99%
“…All thiocarbohydrazide‐ and carbohydrazide‐tethered isatin dimers 42 (Figure 9) were devoid of activity against Herpes simplex virus‐1, Herpes simplex virus‐1 TK‐KOS ACV, Herpes simplex virus‐2, vaccinia virus, vesicular stomatitis virus, and feline herpes virus, whereas two dimers 42a,b (EC 50 : 19.7 and 55.1 μM) were active against the feline herpes virus. [ 98 ] All isatin dimers 43 displayed weak to moderate activity against HIV‐1 (IIIB) with EC 50 values in a range of 13.30 to >238.46 μM, and they were far less potent than the reference azidothymidine (EC 50 : 0.014 μM). [ 65 ] Among them, compound 43a exhibited the highest activity with EC 50 of 13.30 μM, and relatively low cytotoxicity towards MT‐4 cells (CC 50 : 43.85 μM), revealing that it could act as a lead molecule for further optimization.…”
Section: Antiprotozoal and Antiviral Activitymentioning
confidence: 99%